CO2 flux from farmland across salinization gradients during freeze–thaw periods under winter irrigation - Luo, Fan; He, Xinghong; Chen, Yiwei; Gao, Rui; Ma, Yuan; Liu, Shiyuan; Guan, Yao; Ma, Yuying (Frontiers in Plant Science, 2025)
IntroductionWinter irrigation, as an effective agricultural practice, exerts positive effects on spring-sown crops and is widely applied in Xinjiang, China. Under the influence of seasonal freeze–thaw cycles, the mechanisms by which winter irrigation affects farmland carbon emissions are of great significance for both agricultural production and greenhouse gas emissions. Therefore, conducting relevant research is extremely necessary.MethodsA field plot experiment was conducted with three salinity gradient levels. The flood irrigation and drip irrigation were applied during the non-growing period following cotton harvest, with three irrigation amounts.Results and discussionThe results indicated that as the soil froze and thawed, CO2 emissions exhibited a trend of initially decreasing and then increasing. During the pre-freezing period, winter irrigation intensified salt accumulation in the unfrozen zones, thereby restricting gas emissions. The rate of decline in CO2 fluxes increased with irrigation amount, and this effect became more pronounced as soil salinity increased. In the high- and medium-salinity treatments, irrigation significantly reduced CO2 emissions, with the emissions under the irrigation treatments being approximately half of those observed in the control treatment. However, during the thawing period, the redistribution of soil salt and moisture weakened the effect of irrigation and irrigation no longer had no significant effect on CO2 emissions. The soil salinity became the only influential factor. Moreover, since CO2 emissions during the thawing period were much higher than those during the pre-freezing period, the overall effect of winter irrigation on CO2 emissions across the entire freeze–thaw cycle was not significant. From the perspective of carbon sequestration and emission reduction, winter irrigation is a neutral agricultural practice, neither reducing carbon emissions nor increasing the risk of carbon release.